2003
DOI: 10.1289/ehp.5203
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear waste transportation: case studies of identifying stakeholder risk information needs.

Abstract: The U.S. Department of Energy (DOE) is responsible for the cleanup of our nation's nuclear legacy, involving complex decisions about how and where to dispose of nuclear waste and how to transport it to its ultimate disposal site. It is widely recognized that a broad range of stakeholders and tribes should be involved in this kind of decision. All too frequently, however, stakeholders and tribes are only invited to participate by commenting on processes and activities that are near completion; they are not incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…The public is a highly heterogeneous group (Wester-Herber, 2004) and what might be important for one group may not be relevant for another. There are numerous studies indicating which concerns are most common among parts of the public (Drew et al, 2003;Hansen et al, 2003) and also a number of studies and suggestions on how risk communication is best achieved (Frewer, 2004;Grey & Ropeik, 2002) that could serve as a useful tool at an early stage in planning a remediation project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public is a highly heterogeneous group (Wester-Herber, 2004) and what might be important for one group may not be relevant for another. There are numerous studies indicating which concerns are most common among parts of the public (Drew et al, 2003;Hansen et al, 2003) and also a number of studies and suggestions on how risk communication is best achieved (Frewer, 2004;Grey & Ropeik, 2002) that could serve as a useful tool at an early stage in planning a remediation project.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that transparent and open risk assessments, and the communication thereof, can improve relations with a community and make policy issues closer to citizens concerns (European Commission (EC), 2001). This is true even under conditions of uncertainty, as studies have shown that lay people are certainly capable of understanding complex technical information and issues of uncertainty (Drew et al, 2003;Frewer, 2004). However, definitions of key terms, such as risk, differ between experts and lay people (Sj枚berg, 2002).…”
Section: Risk Perception and Risk Communicationmentioning
confidence: 99%
“…The health risk assessment of potential ecological and health risk rising from the planned industrial transport and the treatment of waste at facilities and other industrial and construction activities is paramount [14]. Of course, the public health processes and procedures of such waste management and industrial activities as such cited projects are primarily controlled, regulated and approved by district or regional public health and state authorities, within the scope of prevention of risk, health supervision and best practices.…”
Section: Assessment Of Ecological and Health Risk Factors And Settingsmentioning
confidence: 99%
“…Tribal governments are interested in integrating cleanup and future land use, decreasing effects on human health and the environment, and understanding effects of contamination and cleanup on their usual and accustomed treaty rights (Tano et al, 1996; Harris and Harper, 1997, 2008; Goldstein et al, 2000; Nez Perce Tribe, 2003; Drew et al, 2003; Harper et al, 2008). DOE and others recognized the importance of building consensus (NRC 1994), and of turning extensive and diverse opinions about future use of the site into a comprehensive future land-use plan that was developed as an Environmental Impact Statement under the guidelines of the National Environmental Policy Act (NEPA) (DOE, 1999, revised 2008).…”
Section: Case Studies: Points Of Confusion For Tribal Nations Govmentioning
confidence: 99%